THE INFLUENCE OF EMPLOYEE COMPETENCE AND RISK MANAGEMENT SYSTEMS ON THE QUALITY OF FINANCIAL STATEMENTS AT THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY (BPKAD) OF WEST SERAM REGENCY - Siti Khotijah; Mohamad Arsad Rahawarin; Hendry Selanno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the influence of employee competence and the risk management system on the quality of financial statements at the Regional Financial and Asset Management Agency of West Seram Regency. High-quality financial reporting is essential to ensure transparency, accountability, and effective regional governance. However, recurring audit findings related to asset administration, reconciliation processes, and documentation indicate weaknesses in both human resource capacity and risk control mechanisms. Therefore, this research examines how these two factors contribute to improving financial reporting quality. The study employs a quantitative approach with an associative design. Data were collected through structured questionnaires distributed to all 52 employees involved in financial management and reporting processes, using a saturated sampling technique. The data were analyzed using multiple linear regression, supported by validity and reliability tests as well as classical assumption tests. Hypothesis testing was conducted through t-tests to measure partial effects, an F-test to assess simultaneous effects, and the coefficient of determination to evaluate explanatory power. The results indicate that employee competence has a positive and significant effect on financial statement quality. The risk management system also has a positive and significant effect. Simultaneously, both variables significantly influence financial reporting quality, with a very high coefficient of determination, indicating strong explanatory power. The study concludes that improving employee competence and strengthening risk management systems in an integrated manner are essential strategies for enhancing the reliability, transparency, and accountability of regional financial reporting.